Screening of chickpea genotypes against five races of Ascochyta rabiei causing chickpea blight - MAHENDRA PAL, RAM SINGH* and (Indian Phytopathology, 2002)
Out of 81 chickpea genotypes screened against five races of Ascochyta rabiei, none was resistant to all the races. Two genotypes GG 715 and ACC 76 were resistant to three races while three H 86-8, H 86- 100 and HK 86-120 were resistant to two races.